Constitutional Law: Government of Malaysia v. Lionel - Nijar, Gurdial Singh (Journal of Malaysian and Comparative Law, 1974)
(1974) 1 (1) JMCL 8 Case Notes Constitutional Law: Government of Malaysia v. Lionel - Gurdial Singh Nijar